Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/2017gc007168
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure Geophysical Properties of Fcc Phase FeHX

Abstract: Face centered cubic (fcc) FeHX was synthesized at pressures of 18–68 GPa and temperatures exceeding 1,500 K. Thermally quenched samples were evaluated using synchrotron X‐ray diffraction (XRD) and nuclear resonant inelastic X‐ray scattering (NRIXS) to determine sample composition and sound velocities to 82 GPa. To aid in the interpretation of nonideal (X ≠ 1) stoichiometries, two equations of state for fcc FeHX were developed, combining an empirical equation of state for iron with two distinct synthetic compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 55 publications
9
39
0
Order By: Relevance
“…When plotted as a function of pressure, the computed v P of Fe 0.91 Ni 0.09 and Fe 0.8 Ni 0.1 Si 0.1 from NRIXS results show negligible differences with our re-analysis of similar data for hcp-Fe (Murphy et al, 2013). The computed v P of Fe 3 S (Lin et al, 2004) trends ∼4% below hcp-Fe, while the v P of iron-hydrides (computed from NRIXS (Mao et al, 2004;Thompson et al, 2018); constrained from phonon dispersion measurements (Shibazaki et al, 2012)) trend above hcp-Fe. Although the v P values of Fe 3 C also trend higher than hcp-Fe (Fiquet et al, 2009;Gao et al, 2008;Chen et al, 2018), the value constrained from phonon dispersion measurements around 70 GPa (Fiquet et al, 2009) is significantly higher than the trend computed from NRIXS (Gao et al, 2008).…”
Section: Other Light Elementssupporting
confidence: 40%
See 1 more Smart Citation
“…When plotted as a function of pressure, the computed v P of Fe 0.91 Ni 0.09 and Fe 0.8 Ni 0.1 Si 0.1 from NRIXS results show negligible differences with our re-analysis of similar data for hcp-Fe (Murphy et al, 2013). The computed v P of Fe 3 S (Lin et al, 2004) trends ∼4% below hcp-Fe, while the v P of iron-hydrides (computed from NRIXS (Mao et al, 2004;Thompson et al, 2018); constrained from phonon dispersion measurements (Shibazaki et al, 2012)) trend above hcp-Fe. Although the v P values of Fe 3 C also trend higher than hcp-Fe (Fiquet et al, 2009;Gao et al, 2008;Chen et al, 2018), the value constrained from phonon dispersion measurements around 70 GPa (Fiquet et al, 2009) is significantly higher than the trend computed from NRIXS (Gao et al, 2008).…”
Section: Other Light Elementssupporting
confidence: 40%
“…We compare our reported Figure 12. We include NRIXS studies on Fe 3 S (Lin et al, 2004), Fe 3 C (Gao et al, 2008;Chen et al, 2018), Fe 7 C 3 (Chen et al, 2014), FeO, (Mg 0.06 Fe 0.94 )O, (Mg 0.16 Fe 0.84 )O (Wicks et al, 2017), FeH x (Mao et al, 2004), and FeH x (Thompson et al, 2018). We also include IXS studies on Fe 3 C (Fiquet et al, 2009) and FeH x (Shibazaki et al, 2012).…”
Section: Other Light Elementsmentioning
confidence: 99%
“…Assuming carbon is a sole light element, 1.8-7.7 wt% C has been proposed to account for the outer core density and sound velocity (Sata et al, 2010;Badro et al, 2014Morard et al, 2017). Experimental and theoretical studies demonstrated that they are also reconciled with 0.8-2.0 wt% H in molten iron (Terasaki et al, 2012;Thompson et al, 2018;Umemoto & Hirose, 2015). The green region in Figure 2 shows the possible compositional range of the Fe-C-H liquid core supposed from these studies.…”
Section: Hydrogen Limits the Solubility Of Carbon In Liquid Ironmentioning
confidence: 98%
“…In contrast, earlier experiments on Fe‐H alloys are limited even for solids (e.g., Fukai, ; Pépin et al, ), in particular at high temperatures (Fukai et al, ; Sakamaki et al, ; Terasaki et al, ). While Terasaki et al () reported that solid Fe 3 C does not incorporate hydrogen at 14 GPa, Narygina et al () demonstrated that Fe 3 C was once formed from Fe + C n H 2n+2 paraffin and then replaced by FeH + C diamond at >1600 K and 54 GPa (Ohta et al, ; Thompson et al, ). These results indicate that (1) carbon and hydrogen do not coexist in solid Fe and (2) hydrogen is more siderophile than carbon at relatively high pressure and temperature ( P‐T ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of iron-enriched hydrous pyrite-type phase would reduce the speed of seismic waves at the core-mantle boundary, which may be detected at large low shear velocity provinces and ultra-low velocity zones [11][12][13]. Reservoirs of H also produce hydrides that would possibly infiltrate to the outer core [9,14]. Although H is an influential volatile component, the budget of H in the lower mantle is still under debate [15].…”
Section: Introductionmentioning
confidence: 99%